Preparation and characterization of lanthanum phosphate nanosparticles by solgel spin coating method / Zainurul Atikah Zakaria - Zakaria, Zainurul Atikah (2020)
The sol-gel method was used to prepare LaPO4 nanoparticles as the intimate mixing of the chemical in ensuring homogeneity of the product. Besides, sol-gel methods also have much compensation compared to other methods such as easy coating of large surfaces, low processing temperature and also simple and cheap experiment set-ups. In this work, a sol-gel spin coating method was adopted to prepare LaPO4 nanoparticles with good morphologies. NH4H2PO4 and La(NO3)3.6H2O were used as a precursor or starting material. C10H16N2O8 (EDTA) and C6H8O7 were used as the chelating agent in the starting solution, while NH3 solution was used as a solvent. LaPO4 nanoparticles have been successfully prepared with different concentrations, 0.01, 0.03, 0.05, 0.08 and 0.10 mol of EDTA under constant calcinations temperature, 500oC. The morphology of LaPO4 nanostructures deposited on glass substrate shows nano-rice, nano-sphere, and nano-particle structures. A size of sphere-like structures is smallest at concentration of EDTA 0.05 molar. The intensity of photoluminescence was found to be increased as the concentration of EDTA increased, and LaPO4 prepared at 0.05 mol concentration of EDTA has higher intensity. This is due to highest intensity of bonding existed. Next, the calcinations temperature to produce thin film LaPO4 nanostructure was varied at; 200, 300, 400, and 500oC. FESEM results show that at lower annealing temperatures, 200oC and 300oC, the ricelike structures of LaPO4 was formed and when the temperatures were increased to 400oC and 500oC, the LaPO4 started to form a spherical shape. The intensity of photoluminescence was found to be decreased as the calcinations temperature increased and 400oC showed higher intensity compare to others. The peak shifted to the left for calcinations temperature 400oC and the shifting of the peak to the right at 500oC.Using the same sample preparation condition of 0.05 molar concentration of EDTA and 400oC calcinations temperature, the number of LaPO4 coating layer were varied to 1, 3 and 5. Different coating on the glass will contribute to the different sizes and morphologies of the LaPO4 nanostructures thin film. With increasing number of layers, the particles appear to stick together and this increases the density of nanoparticles formed on surface. The intensity of photoluminescence was found to be decreased as the number of layers increased and 1 layer showed the higher intensity. When the number of layers increased, the peak was shifted to the left and photon emission energy recorded was increased.